Transformational Leadership Construction of High School Principals in Raja Ampat Regency: A Grounded-Theory Case Study in an Archipelagic Context - Sauyai, Stanly Fictor Metem; Palilingan, Rolles N.; Tambingon, Henny Nikolin; Umbase, Ruth (International Journal of Information Technology and Education, 2025)
This study describes and analyzes the construction of transformational leadership among high school (SMA) principals in Raja Ampat Regency and identifies determinant factors shaping that construction within an archipelagic and remote-area setting. The research employs a qualitative case study design and applies grounded-theory procedures to generate an empirically grounded leadership construction model. Data were gathered through in-depth interviews, observation, and document analysis, involving principals as main informants and teachers as supporting informants. Findings show that transformational leadership is constructed through eight interrelated dimensions manifested in daily leadership practices: (1) work direction, (2) communication of vision and mission, (3) trust building, (4) creativity development, (5) motivation provision, (6) role modeling, (7) optimism cultivation, and (8) instilling pride in the school. The construction of transformational leadership is influenced by two groups of determinant factors: internal factors (personal values, motivation, experience, competence, and self-reflection) and external factors (training, teacher support, professional interactions, educational policy, and the socio-cultural context of the archipelago). The study contributes a contextual leadership construction model relevant for remote and island-based education systems and offers implications for principal capacity development and policies to improve educational quality in geographically constrained regions.